Comparative evaluation of dental and Cephalometric skeletal characteristics in the sagittal and vertical plane - Cheong, Joo Ming; Zaharul, Fatin Nabihah; Abdul Hamid, Hanis Izzati; Mohd Ibrahim, Mohamad Shafiq; Mohd Ali, Azrul Safuan (2022)
Introduction: Clinical information regarding skeletal and dental characteristics are essential for orthodontic diagnosis and treatment planning. Therefore, an evaluation to predict the association between skeletal and dental variables would prove diagnostically invaluable.